Miscarriage in COVID-19 Infection: a case report - Yanti, Linda; Susanti, Dwi (MEDISAINS, 2021)
Background: Data on miscarriage in pregnant women with COVID-19 are still limited, as well as the mechanism that causes miscarriage in women with COVID-19. This study aims to report the mechanism of miscarriage that occurs in patients with COVID-19 from various literature.Case presentation: We reported a case of miscarriage occurred in a woman aged 28 years, 11-week pregnancy with COVID-19 in Batin Mangunang Regional General Hospital, Lampung Province, Indonesia.Conclusion: Pregnant women infected with COVID-19 are at risk for miscarriage.